2017
DOI: 10.4187/respcare.04929
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 2 Respiratory Devices for Sputum Clearance in Adults With Non-Cystic Fibrosis Bronchiectasis

Abstract: Both devices were well-tolerated and successfully augmented secretion clearance. Most subjects preferred the Flutter because of increased speed of secretion clearance, and greater ease of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Sputum volume has been assessed in airway clearance studies using different methods including sputum wet weight [41][42][43][44], dry weight [42], the volume collected during and/or immediately following an intervention [35,[41][42][43][44][45][46] or the volume collected in a 24-h period post-intervention [35,41,43]. Studies of airway clearance in bronchiectasis report variations in results on sputum volume.…”
Section: Sputum Volumementioning
confidence: 99%
See 4 more Smart Citations
“…Sputum volume has been assessed in airway clearance studies using different methods including sputum wet weight [41][42][43][44], dry weight [42], the volume collected during and/or immediately following an intervention [35,[41][42][43][44][45][46] or the volume collected in a 24-h period post-intervention [35,41,43]. Studies of airway clearance in bronchiectasis report variations in results on sputum volume.…”
Section: Sputum Volumementioning
confidence: 99%
“…Studies of airway clearance in bronchiectasis report variations in results on sputum volume. Most studies document an increase in sputum volume with use of ACTs [35,43,45,46] but some report inconsistent findings between different studies depending on when sputum volume was measured [35,42,43], while other studies found no benefit on sputum volume with different ACT interventions [41,42,44]. These variations may be due to different study populations, variations in ACTs applied and the sputum measurement time-periods.…”
Section: Sputum Volumementioning
confidence: 99%
See 3 more Smart Citations